2020
DOI: 10.1002/smll.202001770
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating of Lanthanides Ions into Perovskite Film for Efficient and Stable Perovskite Solar Cells

Abstract: Since Yan's work, incorporation of some lanthanide elements, such as Eu and Nd, into MAPbI3 layer has been proven to be a powerful strategy on improving the permanence of the perovskite solar cells (PSCs). However, a comprehensive configuration has not been given for different lanthanide elements doping while the mechanism has not been clarified. Herein, the incorporation of various lanthanides ions (Ln3+ = Ce3+, Eu3+, Nd3+, Sm3+, or Yb3+) into perovskite films to largely enhance the performance of PSCs is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 44 publications
0
72
0
Order By: Relevance
“…Al 3+ , Fe 3+ , Ce 3+ , Yb 3+ , and Bi 3+ ) into LHPs is a promising route to improving their stability. [101][102][103][104] However, the carrier lifetimes all become shorter following doping. [104][105][106][107][108][109][110] Aside from the explanation concerning defects, 111 the experimental results can be rationalized by our proposed simpler model (eqn (1)).…”
Section: Elemental Mixing and Dopingmentioning
confidence: 99%
“…Al 3+ , Fe 3+ , Ce 3+ , Yb 3+ , and Bi 3+ ) into LHPs is a promising route to improving their stability. [101][102][103][104] However, the carrier lifetimes all become shorter following doping. [104][105][106][107][108][109][110] Aside from the explanation concerning defects, 111 the experimental results can be rationalized by our proposed simpler model (eqn (1)).…”
Section: Elemental Mixing and Dopingmentioning
confidence: 99%
“…To better understand the photovoltaic mechanism, the photovoltaic performance, electronic structure, band gap, effective mass of the electron and hole, and the total and partial densities of state have been studied on the basis of experimental results and the first-principles calculation using density functional theory (DFT). [44][45][46] The partial replacement of the europium ion with the B site in the perovskite crystal prevented the decomposition, improving the long-term stability of the performance with the reduction of the internal defect, while suppressing the degradation by the Eu 2+ -Eu 3+ redox shuttle reaction.…”
Section: Introductionmentioning
confidence: 99%
“…After that, RE ions has been incorporated into different perovskite systems, such as CsPb(Cl/Br) 3 , CsPbBr 3 , CsPbI 3 , MAPbI 3 , double perovskite NCs, etc. [37][38][39] Many investigations have reported to illustrate the substitution site of RE ions in the lead halide perovskite NCs. Zhang's group studied a series of CsPbBr 3 : RE (RE = Ce 3+ , Pr 3+ , Nd 3+ , Sm 3+ , Eu 3+ , Gd 3+ , Tb 3+ , Dy 3+ , Ho 3+ , Er 3+ , Tm 3+ , Yb 3+ ) compounds by first-principles calculations, [131] which revealed that RE ions preferred to replace Pb 2+ site, and Yb 3+ and Eu 3+ ions were easier to substitute Pb 2+ due to their close radius.…”
Section: Substitution Site Of Re Ionsmentioning
confidence: 99%
“…[45] RE ions doped organic-inorganic lead halide perovskite were frequently applied to the field of optoelectronics, especially for perovskite solar cells (PSCs). [39,[46][47] In order to enhance the lasing performance of organicinorganic perovskite NCs, Karunakaran's group introduced Tm 3+ in the organic-inorganic perovskite (GAPbI 3 : GA = C(NH 2 ) 3 ). [48] The introduction of Tm 3+ improved the film quality, smoothed the surface, and improved the optical properties of the NCs.…”
Section: Substitution Site Of Re Ionsmentioning
confidence: 99%
See 1 more Smart Citation